IMPLEMENTATION OF QUANTUM PHYSICS INTRODUCTION AID ON VIRTUAL LABORATORIES TO IMPROVE PROFICIENCY GENERIC - Sondang R Manurung; Mara Bangun Harahap; Nuryani Y Rustaman; Benny Suprapto Brotosiswoyo (Jurnal Kependidikan, 2018)
This study was aimed at determining the results of virtual laboratory implementation in the introduction of quantum physics in improving the generic proficiency of prospective teacher students. The research method used was quasi-experimental with pretest-posttest control group design. This design uses the determination of equivalent subjects between the experimental group and purposive control. This learning module consists of 2 types, namely computer program aided module that display the visualization of quantum physics symptoms and conventional learning modules. This study was carried out on a teacher training institution in Bandung, West Java. The research subjects were the sixth semester students of Physics Education in the Subject of Quantum Physics, year 2014/2015. The sample in the experimental group consisted of 15 students, while the control group consisted of 24 students. The experimental group students received the learning of quantum physics with a virtual laboratory, while the control group received conventional learning. The result shows that the use of virtual laboratories in the introduction of quantum physics is able to improve the generic skills of students.IMPLEMENTASI LABORATORIUM VIRTUAL DALAM PEMBELAJARAN PENDAHULUAN FISIKA KUANTUM UNTUK MENINGKATKAN KEMAHIRAN GENERIKAbstrakPenelitian ini bertujuan untuk mengetahui hasil implementasi laboratorium virtua dalam pembelajaran Pendahuluan Fisika kuantum dalam meningkatkan kemahiran generik mahasiswa calon guru. Metode penelitian adalah eksperimen semu dengan pretest-posttest Control Group Design. Desain ini menggunakan penetapan subjek setara antara kelompok eksperimen dan kontrol secara purposif. Modul pembelajaran ini terdiri dari 2 jenis yakni modul yang mempergunakan program komputer yang menampilkan visualisasi gejala fisika kuantum dan modul pembelajaran konvensional. Penelitian ini dilaksanakan di LPTK di Kota Bandung Jawa Barat dengan subjek penelitian mahasiswa Semester VI Jurusan Pendidikan Fisika pada Mata Kuliah Fisika Kuantum Tahun Akademik 2014/2015. Sampel penelitian dalam kelompok eksperimen terdiri dari 15 orang mahasiswa. Kelompok kontrol terdiri dari 24 orang mahasiswa. Mahasiswa kelompok eksperimen menerima pembelajaran fisika kuantum dengan laboratorium virtual. Kelompok kontrol menerima pembelajaran konvensional. Hasil penelitian menunjukkan bahwa penggunaan laboratorium virtual dalam pembelajaran pendahuluan fisika kuantum dapat meningkatkan kemahiran generik mahasiswa.